2023
DOI: 10.1038/s41598-023-37817-3
|View full text |Cite
|
Sign up to set email alerts
|

Nickel ferrite nanoparticles doped on hollow carbon microspheres as a novel reusable catalyst for synthesis of N-substituted pyrrole derivatives

Abstract: Pyrroles are widely spread worldwide because of their critical applications, especially pharmacology. An expedition method for one-pot synthesis of N-substituted pyrrole derivatives has been presented by a reaction between 2,5-dimethoxytetrahydrofuran and various primary aromatic amines in the presence of NiFe2O4 anchored to modified carbon hollow microspheres (NiFe2O4@MCHMs) as a recoverable reactive catalyst. The Classon-Kass method has been used to synthesize the pyrroles in excellent yields and short react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 62 publications
(49 reference statements)
0
5
0
Order By: Relevance
“…SiO 2 @C showed vibration peaks at 1100–1080, 760, and 450 cm –1 assigned to the asymmetric and symmetric stretching and bending modes of Si–O–Si, respectively, as the characteristics of the silica core . After removing the silica core of HC by NaOH etching, these silica characteristics were completely invisible by FTIR, indicating the successful removal of the silica core. , After the impregnation of thymol on the nanosphere surfaces, vibrational bands were observed at 1417 and 804 cm –1 , related to the phenyl ring . This FTIR result indicated that thymol was successfully introduced onto the surfaces of the carbon-based nanospheres.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…SiO 2 @C showed vibration peaks at 1100–1080, 760, and 450 cm –1 assigned to the asymmetric and symmetric stretching and bending modes of Si–O–Si, respectively, as the characteristics of the silica core . After removing the silica core of HC by NaOH etching, these silica characteristics were completely invisible by FTIR, indicating the successful removal of the silica core. , After the impregnation of thymol on the nanosphere surfaces, vibrational bands were observed at 1417 and 804 cm –1 , related to the phenyl ring . This FTIR result indicated that thymol was successfully introduced onto the surfaces of the carbon-based nanospheres.…”
Section: Resultsmentioning
confidence: 85%
“… 19 After removing the silica core of HC by NaOH etching, these silica characteristics were completely invisible by FTIR, indicating the successful removal of the silica core. 20 , 21 After the impregnation of thymol on the nanosphere surfaces, vibrational bands were observed at 1417 and 804 cm –1 , related to the phenyl ring. 22 This FTIR result indicated that thymol was successfully introduced onto the surfaces of the carbon-based nanospheres.…”
Section: Resultsmentioning
confidence: 99%
“…Our research team is currently engaged in the study of catalytic reactions as part of our ongoing research efforts [27][28][29][30] , this study investigated the fabrication and identi cation of CuFe 2 O 4 /g-C 3 N 4 nanocomposite in simple procedure. Moreover, the application of this nanocomposite was carried out as effective reusable catalyst for synthesis of spirooxindol quinazolinone derivatives under mild conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In continuation of our ongoing research works on catalytic reactions, 26–31 in this work, we chose to look into the straightforward and efficient synthesis of indeno[1,2- b ]indolones utilizing a novel effective heterogeneous nanocatalyst. Initially, copper ferrite nanoparticles were prepared by the co-precipitation method; then, the magnetic nanoparticles of the CuFe 2 O 4 @CS-SB nanocomposite were prepared by chelating on the surface of chitosan and a Schiff base.…”
Section: Introductionmentioning
confidence: 99%